Letter (copy) : Capture of Mr. McMahon and Mr. Boyd in Madrid - Citrine, Walter, 1887-1983
010-0055-001 WMC/FEM/MT/165 Secretary's 11th November, 1936. Alderman Midgley, 19, Garfield Chambers, Royal Avenue, BELFAST. Dear Alderman Midgley, Capture of Mr. McMahon and Mr. Boyd in Madrid. Since writing to you on the 9th November, I have heard from the Foreign Secretary, Mr. Eden, that the British Ambassador at Hendaye has already been asked to obtain information regarding these two men, and if the reported arrest is confirmed, to seek their early release. I thought you would like this news. Of course, you will have seen the statements in the press regarding the question that was asked by Mr. Tom Johnston and Viscount Cranborne's reply on the 9th November to the effect that the authorities at Bourgos had been approached that day with a view to securing the men's release. Yours sincerely, General Secretary. 292/946/10/58